Oral Tradition and Synoptic Verbal Agreement : Evaluating the Empirical Evidence for Literary Dependence. - Derico, T. M. (Eugene : Wipf and Stock Publishers, 2016)
New Testament scholars routinely claim that verbal agreement among parallel Synoptic pericopae is a reliable indicator of literary borrowing by the Synoptic Evangelists. In Oral Tradition and Synoptic Verbal Agreement, T.M. Derico presents a critical assessment of that claim through a consideration of the most recent empirical evidence concerning the kinds and amounts of verbal agreement that can be produced among independent performances of oral traditions.
Pages:1 to 25; Pages:26 to 50; Pages:51 to 75; Pages:76 to 100; Pages:101 to 125; Pages:126 to 150; Pages:151 to 175; Pages:176 to 200; Pages:201 to 225; Pages:226 to 250; Pages:251 to 275; Pages:276 to 300; Pages:301 to 325; Pages:326 to 350; Pages:351 to 375; Pages:376 to 378.
Print version record.
Added to collection customer.56279.3 - Master record variable field(s) change: 072, 630, 650
Keywords: Bible. -- Criticism, Textual; Criticism, interpretation, etc; Synoptic problem; Oral tradition; RELIGION / Biblical Studies / Jesus, the Gospels & Acts; RELIGION / Biblical Studies / New Testament; Electronic books